2021
DOI: 10.1088/1755-1315/817/1/012078
|View full text |Cite
|
Sign up to set email alerts
|

Mineral and geochemical characteristics of soils and bottom sediments in the area affected by mining dumps (a case study of the Sibay ore deposit)

Abstract: The article focuses on the chemical composition of hydrosulfates formed in bottom sediments and soils as a consequence of sulfide minerals oxidation in mining waste rock dumps. An alkaline geochemical barrier formed under the dumps reduces pollution of natural-territorial complexes. High concentrations of Zn up to 1.29%, Cu-0.74%, and Cd-27.3 mg/kg are found in the hydrosulfates formed in the river bottom and in the soils. The percentages of exchangeable copper, zinc and cadmium in their total content are 33%,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The study area was located in the eastern part of Yunnan Province, where a large number of IOCG-type iron-copper deposits were distributed [ 77 ]. The parent rocks were characterized by rich iron and high copper, which easily cause the enrichment of Cu, Ni and Zn during the development of the soils [ 78 ]. Therefore, factor 4 was a mining activity source.…”
Section: Resultsmentioning
confidence: 99%
“…The study area was located in the eastern part of Yunnan Province, where a large number of IOCG-type iron-copper deposits were distributed [ 77 ]. The parent rocks were characterized by rich iron and high copper, which easily cause the enrichment of Cu, Ni and Zn during the development of the soils [ 78 ]. Therefore, factor 4 was a mining activity source.…”
Section: Resultsmentioning
confidence: 99%
“…However, because of the intense variation in the grade and thickness, the copper mines currently have no mining value. The soil developed from copper-rich parent rocks is easy to enrich Cu [ 55 ]. Therefore, it can be concluded that Cu in the soil of the study area is affected by the copper mines in the Emeishan basalt.…”
Section: Results and Analysismentioning
confidence: 99%